From fish to modern humans - comparative anatomy, homologies and evolution of the pectoral and forelimb musculature - Diogo, R. (2009)
In a recent paper Diogo and Abdala reported the results of the first part of a research project on the comparative anatomy, homologies and evolution of the pectoral muscles of osteichthyans (bony fish + tetrapods). That report mainly focused on actinopterygian fish, but also compared these fish with certain non-mammalian sarcopterygians. This paper, which reports the second part of the research project, focuses mainly on sarcopterygians, and particularly on how the pectoral and forelimb muscles have evolved during the transitions from sarcopterygian fish and non-mammalian tetrapods to monotreme and therian mammals and namely to humans. The data obtained by our own dissections of all the pectoral and forelimb muscles of representative members of groups as diverse as sarcopterygian fish, amphibians, reptiles, monotremes and therian mammals such as rodents, tree-shrews, colugos and primates, including humans, is compared with the information available in the literature. Our observations and comparisons clearly stress that regarding the number of pectoral and forelimb muscles, the most striking transition within sarcopterygian evolutionary history was that leading to the origin of tetrapods. While extant sarcopterygian fish have an abductor and adductor of the fin and a largely undifferentiated hypaxial and epaxial musculature, extant salamanders such as Ambystoma have more than 40 pectoral and forelimb muscles. Contrary to what is often stated in general textbooks, there is no clear increase in the number of pectoral and forelimb muscles within the evolutionary transition that leadto the origin of mammals, and surely not to that leading to the origins of primates and humans.